Evaluasi Infrastruktur Desa Sebagai Dasar Perumusan Strategi Pengembangan Di Lembang Rinding Batu - Siradjuddin, Irsyadi; Anshar, Muhammad; Fitriani (Program Studi Teknik Sipil Universitas Wiralodra, 2025)
Mapping the potential of agropolitan areas from the perspective of basic infrastructure is essential for formulating regional development strategies. This study aims to analyze the availability of basic facilities and infrastructure as well as to formulate development strategies in Rinding Batu Village, Kesu District, North Toraja Regency. The research employed a descriptive quantitative and qualitative approach through infrastructure availability analysis and SWOT analysis. Data were collected through field surveys, questionnaires distributed to 44 respondents, and documentation from related institutions. The results show that the average availability of infrastructure reached 87% and facilities reached 87.8%, with the main weaknesses found in sanitation, drainage, and the suboptimal condition of several facilities. Quantitative SWOT analysis placed Rinding Batu Village in Quadrant I (x = 0.97; y = 1.16), indicating the dominance of strengths and opportunities for sustainable area development. The development strategy is therefore focused on optimizing the advantages of basic infrastructure while improving weaker aspects to support equitable and sustainable development.